(untitled) (The Peerian Journal, 2024)
The article highlights the fact that the preservation of architectural monuments and the use of modern innovations in their repair are more effective. The use of digital technologies in the repair process and the creation of three-dimensional models, laser devices and 3d printing technologies necessary for architectural monuments are described.